Analysis Financial Feasibility Of Intensive Laying Chiken Farm Business (Case Study at UD. Prapta, Manggis, Bali) - I. B. B., Pratama; Sukanata, I W.; Putri, B. R. T. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
The study aims to analyzed the maintenance management, financial feasibility, Break Even Point and sensitivity of layer chicken farm businesses. The research was conducted at UD. Prapta Pesedahan Village, Manggis District, Karangasem Regency, Bali Province, it done for 3 months, from November 2018 to January 2019. The financial feasibility was analyzed using analysis of investment criteria, Pay Back Period, Break Even Point, and sensitivity analysis. The results of this study indicated that the layer chicken farm business in UD. Prapta has implemented good management such as pullet management, cages, feeds, labor, production and health. This farm bussiness is feasible indicated by NPV of Rp. 2.096.377.202,10, IRR 26.53%, and Net B/C 1,40, Pay Back Period reached within 1 year 3 month 14 days, while the Break even Point is reached within 6 years 9 months 22 days. Break even Point is achieved when the eggs production is 6.809.961,19 eggs/year or when the price of eggs is Rp. 1.041,86 /eggs. The results of the sensitivity analysis show that the layer chicken farm business UD. Prapta sensitive to rising feed prices and a decrease of egg prices with sensitivity values ??of 8,87% and 5,68% respectivelly. Keyword: Layer chicken, financial feasibility, sensitivity